2024
DOI: 10.46690/ager.2024.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Research on the optimization formula performance and dust reduction effect of mine dust suppressant based on response surface method

Na Gao,
Tianqin Zhou,
Longzhe Jin
et al.

Abstract: In this study, sodium dodecyl benzene sulfonate, triton, guar gum and sodium polyacrylate are selected as the composite raw materials of dust suppressants through the determination of physical and chemical properties of single components. Design expert software is used to carry out the mixture design, the determination of experimental parameters and the response surface analysis of the sedimentation rate, evaporation resistance property, surface tension, contact angle of coal dust with the reagent. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Medeiros et al [16] used glycerol oligomerization to produce dust suppressants and the test results showed that hexa and heptaglycerol exhibited a good viscosity and dust suppression performance. Moreover, Gao et al [17] adopted the response surface method (RSM) to evaluate the dust reduction effect. The above studies provide scientific evidence to select the proposed materials and method for dust suppressant preparation in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Medeiros et al [16] used glycerol oligomerization to produce dust suppressants and the test results showed that hexa and heptaglycerol exhibited a good viscosity and dust suppression performance. Moreover, Gao et al [17] adopted the response surface method (RSM) to evaluate the dust reduction effect. The above studies provide scientific evidence to select the proposed materials and method for dust suppressant preparation in this study.…”
Section: Introductionmentioning
confidence: 99%